Integrating Surakarta local wisdom into character education: A quantitative study in elementary schools - Waluyo; Firdaus Himawan Raharjo; M. Nurkhafiq; Ridwan Abdul Wahab; Irhamuddin Mahmud (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
This study investigates the extent to which local wisdom predicts the multidimensional character development of elementary school students within a culturally grounded educational context. Despite increasing global emphasis on character education, empirical evidence remains limited regarding how culturally embedded values can be operationalized as measurable predictors of specific character outcomes. Addressing this gap, the study employs a quantitative cross-sectional design involving 300 students selected through stratified random sampling in Surakarta, Indonesia. Data were collected using psychometrically validated instruments measuring local wisdom and four character dimensions: religiosity, responsibility, tolerance, and environmental concern. Multiple regression analysis reveals that local wisdom significantly predicts all dimensions, with the strongest effect on religiosity (β = 0.55, R² = 0.30), followed by responsibility (β = 0.48, R² = 0.24), tolerance (β = 0.40, R² = 0.16), and environmental concern (β = 0.32, R² = 0.10). These findings demonstrate a systematic gradient in which culturally reinforced values are more effectively internalized than those requiring complex behavioral enactment. This study is among the first to empirically validate a multidimensional and culturally specific model that integrates local wisdom into a statistically robust framework of character development. The results extend existing theoretical perspectives by introducing cultural intensity and behavioral complexity as key mechanisms shaping value internalization and action. Practically, the study highlights the need to complement cultural integration with experiential and action-oriented pedagogies, particularly for behavior-driven character domains. Overall, the findings reposition local wisdom as a measurable and strategically significant foundation for designing contextually responsive and globally relevant character education systems.